The quality cure : how focusing on health care quality can save your life and lower spending too - Cutler, David M. (Aaron Wildavsky forum for public policy, 2014)
"In the United States, the soaring cost of health care has become an economic drag and a political flashpoint. Moreover, although the country's medical spending is higher than that of any other nation, health outcomes are no better than elsewhere, and in some cases are even worse. In The Quality Cure, renowned health care economist and former Obama advisor David Cutler offers an accessible and incisive account of the issues and their causes, as well as a road map for the future of health care reform -- one that shows how information technology, realigned payment systems, and value-focused organizations together have the power to resolve this seemingly intractable problem and transform the US health care system into one that is affordable, efficient, and effective."--Provided by publisher